Cytotoxic effect of 2’, 3’-epoxy isocapnolactone and 8-hydroxyisocapnolactone-2’3’-diol isolated from Micromelum minutum (G.Forst.) Wight and Arn. in human T-lymphocyte leukemia CEM-SS cells - Tan, Kar Ban; Mohammed Alitheen, Noorjahan Banu; Yeap, Swee Keong; Ali, Abdul Manaf; Rahmani, Mawardi (Academic Journals, 2009)
2’,3’-Epoxyisocapnolactone and 8-hydroxyisocapnolactone-2’,3’-diol are two bioactive compounds isolated from the leaves of Micromelum minutum. In this study, the induction of apoptosis by 2’,3’-epoxyisocapnolactone and 8-hydroxyisocapnolactone-2’,3’-diol on CEM-SS cells were investigated. The cytotoxicity of 2’,3’-epoxyisocapnolactone and 8-hydroxyisocapnolactone-2’,3’-diol was screened on CEM-SS by using MTT assay. The apoptotic effect of both compounds on CEM-SS was evaluated by using fluorescence and electron microcopies morphological observation and DNA laddering analysis. The inhibition effect of 2’,3’-epoxyisocapnolactone and 8-hydroxyisocapnolactone-2’,3’-diol at 50% of cell population (IC50) was found to be 4.6 µg/ml (13.5 µM) and 3 µg/ml (7.8 µM) on CEM-SS cells, respectively. From DNA fragmentation, Acridine orange and Propidium iodide staining and electron microscope analyses, the compounds were confirmed to have ability in promoting apoptosis. However, the % of apoptosis induced is low and the event is time-dependent. At high concentration of 10 µg/mL,2’,3’-epoxyisocapnolactone and 8-hydroxyisocapnolactone-2’,3’-diol induced necrosis. Furthermore, 8-hydroxyisocapnolactone-2’,3’-diol also exhibited better cytotoxicity compared to 2’,3’-epoxyisocap-nolactone. The induction time for apoptosis by 8-hydroxyisocapnolactone-2’,3’-diol in CEM-SS is earlier than 2’,3’-epoxyisocapnolactone, which is 4 h and 12 h after treatment. Both 2’,3’-epoxyisocapnolactone and 8-hydroxyisocapnolactone-2’,3’-diol are potential as anticancer agent.